International Education in Australia: A Long Way Down - Marginson, Simon (International Higher Education, 2011)
Australian international education is in trouble, and the downgrade is likely to be large and long. Both demand for and the supply of Australian education are trending downwards. The main driver has been changes on the supply side, especially migration resistance in the Australian electorate. Government is reducing both the number of incoming students and of graduates who become permanent migrants. Part of Australia's share of the global student market will be absorbed by English-language competitors.